Poliovirus trafficking toward central nervous system via human poliovirus receptor-dependent and -independent pathway - OHKA, Seii; Nihei, Coh-ichi; Yamazaki, Manabu; Nomoto, Akio (Frontiers in Microbiology, 2012)
In humans, paralytic poliomyelitis results from the invasion of the central nervous system (CNS) by circulating poliovirus (PV) via the blood–brain barrier (BBB). After the virus enters the CNS, it replicates in neurons, especially in motor neurons, inducing the cell death that causes paralytic poliomyelitis. Along with this route of dissemination, neural pathway has been reported in humans, monkeys, and PV-sensitive human PV receptor (hPVR/CD155)-transgenic (Tg) mice. We demonstrated that a fast retrograde axonal transport process is required for PV dissemination through the sciatic nerve of hPVR-Tg mice and that intramuscularly inoculated PV causes paralysis in a hPVR-dependent manner. We also showed that hPVR-independent axonal transport of PV exists in hPVR-Tg and non-Tg mice, indicating that several different pathways for PV axonal transport exist in these mice. Circulating PV after intravenous inoculation in mice cross the BBB at a high rate in a hPVR-independent manner. We will implicate an involvement of a new possible receptor for PV to permeate the BBB based on our recent findings.